2017 46th International Conference on Parallel Processing (ICPP) 2017
DOI: 10.1109/icpp.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Independent Tasks in Parallel under Power Constraints

Abstract: Energy consumption has become a major concern in the recent years and Green computing has arisen as one of the challenges in order to reduce CO 2 emissions in the computing domain. Many efforts have been made to make hardware less energy consuming, reduce cooling energy of data and computing centers by relocating those facilities to cool regions and other. A novel approach to make the computing domain greener is to add renewable energy sources for the power supply. The challenge of this work is to consider com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In this section we present an experimental study of the proposed heuristics. We have developed a python simulator 2 presented in [KNPRS17] that offers a wide range of experimental setups on the parallel computational platform. The simulator takes as input a set of tasks and the green power production, expressed by a set of intervals of time with the available power level at each interval.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section we present an experimental study of the proposed heuristics. We have developed a python simulator 2 presented in [KNPRS17] that offers a wide range of experimental setups on the parallel computational platform. The simulator takes as input a set of tasks and the green power production, expressed by a set of intervals of time with the available power level at each interval.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the power production is limited and intermittent. The challenge is to optimize the use of an available power envelope when scheduling tasks as soon as possible and it can also been solved by minimizing the makespan [KNPRS17,KNPRS18].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding the optimal makespan, the shortest possible time to execute a set of tasks under power constraints, is proven to be NP-Complete in [12] and, by assessing classic list algorithms on this problem, it is shown that the algorithm performance depends on the problem characteristics as mean task duration or power consumption. In this article, we assess the use of genetic algorithms on the problem of scheduling a set of tasks under power constraints to minimize the makespan.…”
Section: Introductionmentioning
confidence: 99%